An Analysis of English Classroom Multimedia Teaching Quality Based on Elite Teaching Optimization Algorithm - Chunhua Zhao; Dongyan Jiang (Advances in Multimedia)
As China is increasingly developing towards internationalization, English has become one of the essential skills for foreign communication. In view of the evaluation of music teaching quality, this paper tries to introduce elite teaching optimization algorithm, use multimedia to assist, sort out the factors affecting English teaching quality to build the corresponding indexes, select and optimize the English teaching quality evaluation model, and finally judge the results of English teaching quality. The simulation results show that the elite teaching optimization algorithm is effective and can support the quality analysis of English classroom multimedia teaching.